FENOMENA PENDISTRIBUSIAN ZAKAT OLEH MASYARAKAT NAGARI TANJUNG - Afrian Raus (JURIS (Jurnal Ilmiah Syariah), 2018)
The phenomenon of distributing moslem tax through meal party in a specific society without giving any differences among wealty people and poor showed that it was different with the way of distributing moslem tax generally according to “Syariah” ways. Society who did this way in this time were the specific people who had cultivation of lands where the their wealty from their ancestor. If it was seen from the society’s needs in general, those societies quite disliked this way because there were a few people in those societies who still did this way. It means that this way was not appropriate to be applied nowadays.